Optimalisasi Angka Partisipasi Sekolah Anak Usia Dini Untuk Meningkatkan Indeks Pembangunan Manusia (Studi Kasus di Provinsi Nusa Tenggara Timur) - Anne Mudya Yolanda; Eva Eriani (Jurnal Statistika Terapan (ISSN 2807-6214), 2022)
Preparing future generations should begin in childhood. Nusa Tenggara Timur (NTT) is a province that still struggles with early childhood school participation rates. In 2020, the school participation rate for children aged 0-6 years by cities/regencies in NTT is 18,03, with a Human Development Index of 65,19. According to K-means clustering analysis, early childhood school participation rates by regencies/municipalities aged 0-6 years by cities/regencies could be grouped into three clusters with 9, 8, and 5 regencies/municipalities, respectively. For aged 5-6 years, it could be classified into three clusters: deficient, fair, and good, with 6, 10, and 6 regencies/municipality, respectively. Kupang, Alor, Ende, Ngada, Malaka, and Kupang municipality are the deficient clusters. Sumba Barat, Sumba Timur, Timor Tengah Selatan, Timor Tengah Utara, Belu, Lembata, Flores Timur, Sumba Tengah, Nagekeo, and Manggarai Timur are all part of the fair cluster. Sikka, Manggarai, Rote Ndao, Manggarai Barat, Sumba Barat Daya, and Sabu Raijua regencies are among those in the good cluster. Based on the k-means clustering analysis, the government could implement a segmented policy to optimize The School Participation Rate for Early Childhood in order to increase the Human Development Index. This optimization could begin by increasing the allocation of education funds, particularly for the establishment of early childhood education programs. Extension programs are required to increase parents' understanding of why their children should attend preschool. Furthermore, the government must provide training in the development of teaching skills and knowledge for educators, both teachers, and practitioners in early childhood education.